Delivery of curcumin by directed self-assembled micelles enhances therapeutic treatment of non-small-cell lung cancer [Corrigendum] - Zhu WT (Dove Medical Press, 2017)
Zhu WT, Liu SY, Wu L, et al. Int J Nanomedicine. 2017;12:2621–2634. On page 2623, under the heading ‘Entrapment effciency (EE) and DL’, the sentence “Acetonitrile/2.5% acetic acid (58/42, v/v) was used as eluent at a flow rate of 1 mL/min” should read “Acetonitrile/0.25% acetic acid (58/42, v/v) was used as eluent at a flow rate of 1 mL/min”. On page 2623, under the heading ‘Cellular uptake of CUR/mPEG–PLA micelles’, first paragraph, the sentence “Subsequently, cells were stained with Hoechst 33258 for 5 minutes, subsequently washed with PBS and fixed with cold 4% paraformaldehyde for 10 minutes” should read "Subsequently, cells were fixed with cold 4% paraformaldehyde for 10 minutes and stained with Hoechst 33258 for 5 minutes”. Read the original article